Constructal law analysis of Cl− transport in eyes aqueous humor - Umberto Lucia (Nature Portfolio, 2017)
Abstract Progressive loss-of-vision related to any intraocular disorder is known as glaucoma. Secretion of aqueous humor is physiologically important to provide nutrients and oxygen to the avascular anterior segment and ensuring normal visual function, even if, nowadays reducing the secretory rate to lower intraocular pressure is a major strategy in treating glaucomatous patients. Understanding the mechanisms and regulation of aqueous humor formation is very important to develop possible new approaches to lower intraocular pressure,but today there isn’t any comprehensive model of the regulation of these component in forming aqueous humor. In this paper Construcal law is used to suggest how the Cl− fluxes can determine the water inflow and outflow, and, consequently, how the intraocular pressure is controlled by these fluxes.